NIR-II Fluorescence Imaging of Skin Avulsion and Necrosis - Li, Yizhou; Hu, Xiang; Yi, Wanrong; Li, Daifeng; Guo, Yaqi; Qi, Baiwen; Yu, Aixi (Frontiers in Chemistry, 2019)
Skin avulsion is commonly seen in individuals exposed to heavy shearing forces. Subcutaneous tissue detachment and bone fractures usually accompany skin avulsion. Thus, the estimation of damaged tissues is very important. Currently, the viability of skin and subcutaneous tissue is determined by clinical observations and these observations always underestimate the true extent of the avulsed skin. Herein, we synthesized an innovative probe, CH1055-GRRRDEVDK (CH1055-GK), which can specifically bind to caspase-3, and image skin avulsion and define necrotic margins. Our apoptotic cell uptake tests and evaluation of the probe ex vivo and in vivo showed that the probe has a strong ability to bind caspase-3 in skin avulsion models and that the probe vividly detected the necrotic area in avulsed skin. Furthermore, the increased fluorescence intensity of the probe in the avulsed skin showed a larger affected area than that determined by clinical observations in live mice. Consequently, our results indicated that the caspase-3-targeted probe CH1055-GK observed by NIR-II imaging allowed the clear detection of skin avulsion in subjects, indicating its potential as an imaging tool for the early diagnosis of skin avulsion and determination of necrotic margins.